Structural analysis of three-dimensional wings using finite element method - Aabid, Abdul; Mohd Zakuanl, Muhammad Amir Mirza; Khan, Sher Afghan; Ibrahim, Yasser E. (Springer Nature, 2021)
This paper investigates the structural behavior of the wing subjected to the aerodynamic loads during the flight using finite element analysis of wing flexure deformation. In this work, three different types of wing models are established. Material characteristics, the wing structure, and 1 design principle have been taken into account. The assembly of the wing model 2 consists of the thin skin, two spars, and the multi-ribs. The two spars consist of primary and secondary spars. For this study, NACA 23015 is chosen as the baseline airfoil as this airfoil is very similar to the customized airfoil being used in Airbus A320. Two spars mainly bear the bending moment and shear force, which are made of titanium alloy to ensure sufficient rigidity. The skin and wing ribs are made of aluminum alloy to lighten the structural weight; a static structural analysis is applied. Total deformation, equivalent elastic strain, and equivalent von Mises stress are obtained to study the wing’s structural behavior. Furthermore, the modal analysis is then applied. The natural frequencies and the modal shape of the wing for three orders are obtained through the pre-stress modal analysis. The modal analysis results help designers minimize excitation on the natural frequencies and prevent the wing from fluttering. According to the results, designers can emphasize strengthening and testing the stress concentration and large deformation area.